Manajemen Program Gerakan Masyarakat Magrib Mengaji di Kecamatan Tempuling Kabupaten Indragiri Hilir - Mikrot Mikrot (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
The Koran is an activity that is closely related to the Muslim community in Indonesia since the beginning of the development of Islam. Maghrib Koran is an activity to cultivate the habit of reading the Koran after the evening prayer among the community both in urban and rural areas. This study aims to determine the management of reading time in Tempuling District, Indragiri Hilir Regency, to determine the factors that support and hinder the Magrib Mengaji program in Tempuling District, Indragiri Hilir Regency. This research is a field research conducted in mosques, mosques and mosques that carry out activities in Tempuling District, Indragiri Hilir Regency using the observation method, 5 people using the interview method and the documentation method. Factors that support the Magrib Recitation program are the majority of community leaders strongly support the Maghrib Koran activities, the form of caring in various ways, sometimes by giving gifts, sitting together in the mosque or prayer room, donating. In terms of the quality of teaching, the time available in mosques and surau is adequate and of good quality, the family and community environment is also very supportive, while the factors that hinder the Maghrib Koran program are the managers of the Maghrib Koran in mosques, mosques and prayer rooms not receiving socialization and manuals. or guidelines on the Koran and Islam, the delay in providing incentives for teachers of the Maghrib Koran and the absence of increased incentives and the lack of facilities and infrastructure that support the Maghrib Koran program.